Multivalued Impulsive SDEs Driven by G-Brownian Noise: Periodic Averaging Result - Mahmoud Abouagwa; Anas D. Khalaf; Nadia Gul; Sultan Alyobi; Al-Sharef Mohamed (Complexity)
This paper aims to study two approximation theorems in view of the periodic averaging results for non-Lipschitz multivalued stochastic differential equations with impulses and G-Brownian motion (MISDEGs). By adopting G-Itô’s formula and non-Lipschitz condition, the solutions to the simplified MSDEGs without impulses may replace those of the initial MISDEGs in view of approximation in L2-sense and capacity. Finally, we bring a couple of two examples to enhance our theoretical results.